Pharmacokinetics of Recombinant Factor IX after Intravenous and Subcutaneous Administration in Dogs and Cynomolgus Monkeys - McCarthy, K.; Stewart, P.; Sigman, J.; Read, M.; Keith, J. C., Jr.; Brinkhous, K. M.; Nichols, T. C.; Schaub, R. G. (Thrombosis and Haemostasis, 2002)
Hemophilia B therapy requires intravenous (IV) infusions of large volumes of factor IX due to the low concentration of factor IX in concentrates (∼100 IU/mL). High concentration recombinant factor IX (rFIX) could be a significant advance since it would reduce the large volumes necessary for IV dosing and allow for low-volume subcutaneous (SC) administration. To evaluate high concentration factor IX, we produced formulations with either 2,000 or 4,000 IU/mL and studied the SC bioavailability in beagle dogs, cynomolgus monkeys and hemophilia B dogs along with efficacy in hemophilia B dogs. Beagle dog SC bioavailability was 86.4% using a 2000 IU/mL formulation and 77.0% using a 4000 IU/mL formulation. Monkey bioavailability of a 4000 IU/mL formulation of rFIX was 34.8%. A single SC administration of 200 IU/kg (4000 IU/mL) of rFIX to hemophilia B dogs, produced factor IX clotting activity above 5% for 5 days with a bioavailability of 48.6%. High concentration SC rFIX has an acceptable pharmacokinetic profile in monkeys and dogs, and produces a sustained FIX activity in hemophilic dogs.
Keywords: Factor IX; hemophilia B; subcutaneous; dogs; cynomolgus monkeys